Penerapan Metode Naive Bayes Dalam Rekomendasi Strategi Penerimaan Peserta Didik Baru - Afan Hafara Sani; Agus Setiawan; Ardhin Primadewi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
New Student Admission (PPDB) is a school spearheading activity in getting students, especially for private schools. SMK Muhammadiyah 1 Borobudur as one of the private vocational schools in Magelang Regency. SMK Muhammadiyah 1 Borobudur has problems related to the PPDB promotion strategy. The PPDB promotion that has been carried out has not fully shown a significant promotion growth to increase the number of students registering each year and PPDB information has not yet reached remote areas of Magelang Regency. In determining the promotion media for PPDB SMK Muhammadiyah 1 Borobudur, this study uses the Naïve Bayes algorithm. Naïve Bayes is a classification method using probability and statistics to predict future opportunities based on the past. By using the nave Bayes algorithm which is applied with a ratio of 70:30 for train data and test data, it is able to produce an accuracy of 72%. To maximize the results of data accuracy, this study used the k-fold cross-validation method with k=10 times resulting in an accuracy of 75%. In addition, it can be seen that 3 PPDB information is recommended for promotional media, namely student partners, alumni and Instagram.